2009
DOI: 10.1037/a0016456
|View full text |Cite
|
Sign up to set email alerts
|

Pitch and time, tonality and meter: How do musical dimensions combine?

Abstract: The authors examined how the structural attributes of tonality and meter influence musical pitch-time relations. Listeners heard a musical context followed by probe events that varied in pitch class and temporal position. Tonal and metric hierarchies contributed additively to the goodness-of-fit of probes, with pitch class exerting a stronger influence than temporal position (Experiment 1), even when listeners attempted to ignore pitch (Experiment 2). Speeded classification tasks confirmed this asymmetry. Temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
95
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(103 citation statements)
references
References 136 publications
(209 reference statements)
6
95
2
Order By: Relevance
“…Metrically stable temporal positions usually correspond to those of tonally stable tones in Western tonal music (Prince et al, 2009).…”
Section: --------------------------------------------------------mentioning
confidence: 99%
“…Metrically stable temporal positions usually correspond to those of tonally stable tones in Western tonal music (Prince et al, 2009).…”
Section: --------------------------------------------------------mentioning
confidence: 99%
“…More recently, Prince, Thompson, and Schmuckler (2008) found an asymmetric relation between pitch and time, with pitch variation influencing temporal judgments, but temporal variation having no impact on pitch judgments. In this study, musically trained listeners heard a simple tonal context consisting of a melody accompanied by supporting chords and a metronome click, followed by a probe tone that varied in its pitch and timing.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, listeners' responses exhibited a congruity effect in which tonally stable probes were reported as occurring at metrically stable positions, and tonally unstable tones were reported as occurring at metrically unstable positions. Prince et al (2008) argued that this asymmetry arises due to a learned, inherent bias in the processing of typical Western tonal music that generally contains more elaborated and compelling pitch variation, relative to rhythmic/temporal variation.…”
Section: Introductionmentioning
confidence: 99%
“…Although some previous work investigating the relationship between tonal orientation and metric hierarchy has used probe tones or timed reaction tasks (Prince et al, 2009), others have employed the more complex decision-making task of matching a stimulus with an accompaniment (Hannon et al, 2004). We adopt the latter approach, with participants matching a metrically-determined musical stimulus with a tonally-orienting harmonization: a dominant seventh.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, in probe-tone experiments, when asked to report whether the heard probe tone occurred on a beat or off a beat, participants tended to report stable tones as being on a beat, even in metrically ambiguous situations (Prince, Thompson, & Schmuckler, 2009). Similarly, Rosenthal and Hannon (2016) found that metrical position affects listeners' ratings of probe-tones after being exposed to whole-tone melodies that followed a non-uniform key profile distribution.…”
mentioning
confidence: 99%